Pembaruan Hukum Islam: Menimbang Tawaran Pemikiran ‘Abd Al-Lâh Ahmad Al-Na’îm - Mutawalli Mutawalli (Universitas Islam Negeri Mataram, 2008)
One of the Islamic doctrines that becomes methodological base for Muslims in the implementation of Islam is ijtihad. This concept, however, is considered valid when it is applied in zhanni areas, not qath¢i ones and Islamic theology. In Islamic terminology, terms syari’ah and fiqh are interesting to be discussed and reformed. Transformative-contextual Islamic thinking reconstruction is greatly needed so that syari’ah exists and is able to become modern constitution. One of the Islamic thinkers who tries to actualize ijtihad as a scientific paradigm in Islamic law reform is Abdullah al-Na’im. He tries to reform Islamic law in facing Western law development, especially in public Islamic law. This writing is constructed to see Al-Naim’s intellectual setting and how he sets ijtihad as scientific paradigm in Islamic law. Hopefully, this writing will give perspectives in facing modern problems.